An Aesthetic Appraisal of Newspaper Coverage of Boko Haram Activities - Udoh, Godspower (Journal of New Media and Mass Communication, 2017)
The International Community and other global bodies have repeatedly issued statements condemning the activities of Boko Haram, a militant organisation which emerged around 2002 as a local Islamic group. The world body has been calling on individuals and institutions, particularly the press, to help in the fight against Boko Haram. However, a typical West African country where the insurgency has as its major flashpoint is Nigeria, whose press, is accordingly used as a case study here. Given the fact that newspapers have a role to play in the fight against Boko Haram, one expects them to be creative in their coverage of the activities of the sect, if their coverage should contribute significantly towards peaceful coexistence. This is where application of aesthetic principles of violent conflict reporting, as identified in this paper, comes in. But have the newspapers been applying the aesthetic indices of violent conflict reporting identified in this paper, while contributing their quota towards the return of peace to the sub-region? An appraisal of the various stories on the activities of Boko Haram in Nigeria within the last two years of the group’s peak activities shows that Nigerian newspapers have been mainly informative and alarmist in their coverage of the activities of the group, and could not strike a balance with the other aesthetic indices. The paper concludes, therefore, that Nigerian newspapers are, to a great extent, mono aesthetic in their coverage of Boko Haram activities, and needs to ensure an aesthetic equilibrium for them to create more impact in the peace process.